Clinical Characteristics and Prognostic Factors of Children With Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Yang, Sai; Yang, Liming; Liao, Hongmei; Chen, Mei; Feng, Mei; Liu, Shulei; Tan, Lihong (Frontiers in Pediatrics, 2021)
Objective: Anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis is the most common autoimmune encephalitis in pediatric patients. The study aimed to investigate the clinical characteristics and prognostic factors of anti-NMDA receptor encephalitis in children in South China. Methods: This was a retrospective study of children diagnosed with anti-NMDA receptor encephalitis between 01/2014 and 12/2017 at Hunan Children’s Hospital. Laboratory, brain magnetic resonance imaging (MRI), and electroencephalography data were collected. The short-term (6-month) outcomes were assessed using the Liverpool score by the same pediatric neurologist. The children were divided into good (score 4-5) and poor (score <3) clinical outcomes. Results: Among the 51 patients, 21 (41.2%) were male. The most common clinical symptoms were dyskinesia (88.2%), personality change (84.3%), seizure (82.4%), and cognitive disorder (31.4%). Two were transferred to another hospital, 45 (91.8%) received intravenous immunoglobulins, 41 (83.7%) received methylprednisolone, and 8 (16.3%) received plasma exchange. Eight (16.3%) received rituximab for second-line treatment, six after intravenous immunoglobulin and methylprednisolone treatment, and two after plasma exchange therapy failed. Seven were lost to follow-up. The short-term outcome was good in 23 patients. Cognitive disorder (odds ratio (OR): 23.97, 95% confidence interval (CI): 1.12-513.30, P=0.042) and abnormal brain MRI (OR: 14.29, 95%CI: 1.36-150.10, P=0.027) were independently associated with a poor short-term outcome after adjustment for age, GCS, and rituximab use. Conclusions: MRI abnormalities and cognitive disorders are independently associated with poor short-term outcomes in children with anti-NMDA receptor encephalitis. The use of rituximab is not associated with the 6-month outcomes.